Analisis Kapasitas Kolam Retensi Untuk Pengendalian Banjir di DAS Buah Kota Palembang - Febrinasti Alia; Sakura Yulia Iryani; Nuzula Ramadhanti (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
According to Public Works Office of Palembang City, Buah Watershed is listed as one of priority areas that require immediate flood management actions. Flat terrain, high rainfall intensity, tidal fluctuation worsens by massive land use change, are major causes that increase surface water runoff. Therefore, retention basins as one of technical solutions are expected to accommodate runoff discharge and reduce flood. This study aims to analyze the existing hydrological conditions of Buah watershed and to simulate the effectiveness of designed retention basins on peak flow reduction. Hydrological analysis using SCS Unit Hydrograph Model, HEC-HMS combine with spatial analysis using GIS in 26 subcatchment areas resulted on peak discharges range from 1,27 m3/s – 15,71 m3/s. Furthermore, there are ​​12 proposed retention basins within study area ranges from ​​0,580 Ha – 3,967 Ha that are designed to reduce the peak discharge. Simulation result of flood discharge reduction using HEC-HMS indicates that the effectiveness of retention basins in proposed locations varies from 0,03% - 80,05% depending on watershed areas, land availability, and the depth of retention basins.